Penguatan Kapasitas Komunitas dalam Mitigasi Bencana Alam dan Covid-19 melalui Kolaborasi Interprofesional di Desa Bedagung, Magetan - Sumasto, Hery; Rahayu, Teta Puji; Suparji, Suparji; Wisnu, Nurwening Tyas; Widyawati , Widyawati; Hupitoyo , Hupitoyo (Health Community Engagement, 2023)
The people of Bedagung Village face double vulnerability to natural disasters (landslides) and non-natural disasters (Covid-19). Through the approach of interprofessional collaboration (IPC) and interprofessional education (IPE), this service activity aims to reduce disaster risk through research-based training and mentoring and cross-institutional and professional cooperation. The activity was carried out for six months in Bedagung Village by involving three Polytechnics (Surabaya, Malang, and Surakarta), local stakeholders, as well as various health and management professions. Activities include the formation of the DESTANISIF Task Force, mitigation training, the latest disaster risk mapping, disaster management simulations, and trauma healing. The results show an increase in community understanding and preparedness in dealing with disasters. This program proves that an interprofessional and community-based approach is effective in building disaster-resilient villages